EFEK METODE PEMBELAJARAN BERBASIS CERITA DAN MEDIA PEMBELAJARAN TERHADAP KEMAMPUAN MEMBACA SISWA SEKOLAH DASAR DI ERA GLOBALISASI - Didit Darmawan; Faridatus Shofa; Hidayatus Sholikhah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In today’s globalized world, reading ability has turned into one of the essential skills that elementary school students must possess. Reading literacy serves as a means to expand knowledge, a foundation for fostering creativity and critical thinking skills in the 21st century. Students who still face challenges in reading skills, if left unaddressed, will impact the quality of human resources in the future. The implementation of story-based learning methods supported by interactive learning media presents an innovative and enjoyable solution to improve reading skills while boosting students' learning motivation. This study aims to examine the extent to which story-based learning methods combined with various learning media can enhance the reading abilities of elementary school students amidst the current wave of globalization. This study uses a Systematic Literature Review (SLR) approach, which includes the stages of identification, selection, evaluation, and synthesis, and is a type of qualitative research. The analysis results show that the application of the storytelling method has a clear positive impact on improving reading literacy skills, reading comprehension, and students' motivation in reading activities. The use of various media such as picture books, digital comics, word cards, flashcards, hand puppets, and interactive digital media has proven to create a fun, communicative, and meaningful learning environment for students. Thus, story-based learning enriched with interactive media can be an effective strategy for improving reading and literacy skills in elementary school students, while also preparing them to face increasingly complex global challenges. Keywords: storytelling method, learning media, reading ability, literacy, elementary school